Technology meets Psychology: Teaching Business Students Critical Thinking within New Learning Formats (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2017)
With the increasing use of technology in education, one may ask if psychological subjects with a huge amount of personal involvement are suitable for teaching within technology based learning formats. The UAS Burgenland redesigned the course “Critical Thinking” for part-time business students to reflect on leadership and intercultural communication using a blended learning format. This paper (presentation) elaborates on the requirements when teaching psychological topics and combining on-campus training with virtual classrooms. Succeeding in this effort means selecting very specific exercises and tasks in the diverse phases, linking them properly, adjusting the feedback processes and being aware of the diverse roles as a coach and moderator. Results have shown that students value the combination of various teaching methods as long as they feel safe within their self-development. Moreover, they are motivated to participate in virtual classrooms as the physical distance provides them with a sense of security in contrast to on-campus classes. The course “Critical Thinking” aims to provide a model for teaching psychological subjects within technology based education.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.